2017
DOI: 10.4172/2153-2435.1000548
|View full text |Cite
|
Sign up to set email alerts
|

Potential Anti-diabetic Effects and Safety of Aqueous Extracts of Urtica dioica Collected from Narok County, Kenya

Abstract: Drug bio screening for potential anti-diabetics is scientifically motivated by the desire to discover newer, safer and affordable drugs that complement conventional strategies for management of diabetes. Urtica dioica grows naturally in many parts of Africa with a wide variety use in traditional medicine and diet. However, scientific validation for use of U. dioica has not been done for anti-diabetic activity. The aim of the study was to determine the antidiabetic effects of aqueous extracts of U. dioica in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…In addition, as organic nitrogenous compounds, amino acids from nettles are building blocks in the process of protein biosynthesis [ 85 ]. The safety of aqueous extracts of U. dioica and their antidiabetic effects have been confirmed with mice models [ 86 ].…”
Section: Urtica Spp In Traditional and Modern mentioning
confidence: 99%
“…In addition, as organic nitrogenous compounds, amino acids from nettles are building blocks in the process of protein biosynthesis [ 85 ]. The safety of aqueous extracts of U. dioica and their antidiabetic effects have been confirmed with mice models [ 86 ].…”
Section: Urtica Spp In Traditional and Modern mentioning
confidence: 99%
“…dioica extract has been studied for several different disease conditions including autoimmune diseases, such as rheumatoid arthritis, allergy, eczema, atherosclerosis, cancer, as well as age-related degenerative brain disorders. It has also been studied for alleviating bladder disorders, hemorrhaging and inflammation [4][5][6]. More recent studies show that U. dioica extract possess anti-diabetic properties [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been studied for alleviating bladder disorders, hemorrhaging and inflammation [4][5][6]. More recent studies show that U. dioica extract possess anti-diabetic properties [5][6][7]. A comprehensive review on studies using the extract as intervention for diabetes shows that over 21 studies [7].…”
Section: Introductionmentioning
confidence: 99%
“…The nettle leaves contain a significant number of biologically active compounds, such as terpenoids, carotenoids including β-carotene, neoxanthin, violaxanthin, lutein and lycopene, fatty acids, especially palmitic, cis-9,12-linoleic and α-linolenic acids, different polyphenolic compounds, essential amino acids, chlorophyll, vitamins such as A, B, C, E and K, tannins, carbohydrates, sterols, polysaccharides, isolectins and minerals [7][8][9][10][11][12][13][14][15][16][17][18][19]. Scientific studies have shown that Urtica dioica extracts have antimicrobial, anti-inflammatory, antidiabetic, and anti-aging effects, which is associated with the content of phenolic compounds in them [20][21][22]. Phenolic compounds are famous group of secondary metabolites with wide pharmacological activities [23].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroalcoholic extract of Urtica dioica showed positive in-vitro antioxidant activity and nettle was described as natural antioxidant that can replace the synthetic ones to be used in foods and cosmetics [31]. In studies on aqueous extracts of nettle biological compounds, antioxidant capacity and their antidiabetic, antimutagenic and hypotensive effects were determined [9, 21,32,33]. Methanolic extracts studies suggested that Urtica dioica has a protective capacity and antioxidant activity against cisplatin toxicity in EAT-bearing mice and can efficiently disslove calcium oxalate renal stones in male Sprague-Dawley rats [34,35].…”
Section: Introductionmentioning
confidence: 99%